2008
DOI: 10.4103/0973-3930.43097
|View full text |Cite
|
Sign up to set email alerts
|

The effect of periodontal therapy on the improvement of glycemic control in patients with type 2 diabetes mellitus: A randomized controlled clinical trial

Abstract: AIMS:The purpose of this study is to investigate the effect of improved periodontal health on glycemic control in type 2 diabetes mellitus (type 2 DM) patients who have generalized periodontitis.MATERIALS AND METHODS:A total of 45 type 2 DM patients with generalized periodontitis were selected for the study. The selected patients were randomly assigned to three groups (groups A, B, and C) comprising 15 patients each: • Group A received treatment with scaling and root planing only. • Group B received treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
109
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 24 publications
8
109
0
1
Order By: Relevance
“…A significant decrease in the HbA1c level relative to the level in the control groupwas observed in the experimental groups (p<0.001) 35) .…”
Section: Search Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A significant decrease in the HbA1c level relative to the level in the control groupwas observed in the experimental groups (p<0.001) 35) .…”
Section: Search Resultsmentioning
confidence: 98%
“…Singh et al 35) reported that significant changes in periodontal indices were observed in experimental groups A and B following the periodontal treatment (p<0.001).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…121 The use of adjunctive systemic doxycycline to SRP therapy improved the periodontal parameters in uncontrolled type 2 DM patients compared to group SRP alone. 120,121 On the contrary, some of the studies did not significantly improve the results. 122,123,125 Moreover, the use of systemic doxycycline as adjunctive therapy in Type 1 DM patients with periodontitis did not improve levels of glycemic control.…”
Section: The Use Of Doxycycline In Diabetes Mellitus With Periodontalmentioning
confidence: 85%
“…95,103 The studies on type I and type II diabetic rats demonstrated that the non-antibiotic properties of TCs were effective in reducing the severity of a variety of abnormalities including (but not limited to) those in collagen structure, turnover and in bone remodeling (both locally in the oral tissues and systemically) that contribute to the pathogenesis of diabetic complications, such as unusually severe periodontitis. 118,119 Singh et al 120 study indicated that protein synthesis Atatürk Üniv. Diş Hek.…”
Section: The Use Of Doxycycline In Diabetes Mellitus With Periodontalmentioning
confidence: 99%